The Construction and Application of Smart Teaching Model for Speaking in International Chinese Language Education: 国际中文智慧口语教学模式构建与应用 - Wenjing, Chen; Xujing, Chen (Published by Confucius Institute UNS, 2024)
In the era of information technology transformation, education requires a digital transformation to meet the diverse learning needs of learners and to cultivate their digital competencies. International Chinese Smart Education is a crucial strategic initiative for advancing the digital transformation of education. There is an urgent need to develop effective teaching models to serve as a bridge between the theory of smart education and teaching practice. This study attempts to integrate the concepts of smart education with a Chinese oral language teaching model, leveraging educational technology to support both students' self-directed learning and teachers' instructional activities. A